The relationship between time management and learning outcomes in Physical Education among Junior High School students - Zaki, Muhammad; Wicahyani, Sri (Sriwijaya Journal of Sport, 2026)
Research Background: Time management skills are considered an important learning competency frequently associated with students’ academic achievement, as they contribute to organizing learning activities, improving learning readiness, and supporting effective task completion. In Physical Education, the learning process emphasizes not only conceptual understanding but also practical skills involving physical activities. These distinctive learning characteristics raise questions regarding whether time management skills are related to PE learning outcomes in both cognitive and psychomotor domains. Research Objective: This study aims to examine the relationship between time management skills and PE learning outcomes among ninth-grade students of SMP Khadijah Surabaya. Methods: This study employed a quantitative approach with a correlational research design. The participants consisted of 154 students selected using a total sampling technique. Data were collected through a time management skills questionnaire and assessments of cognitive and psychomotor learning outcomes aligned with the school curriculum standards. Data analysis was conducted using the Spearman Rank correlation test to identify relationships between research variables. Results: The findings indicated no significant relationship between time management skills and cognitive learning outcomes (r = 0.018; p = 0.829), psychomotor learning outcomes (r = 0.002; p = 0.977), or overall, PE learning outcomes (r = 0.014; p = 0.862). Conclusion: Time management skills are not a primary factor influencing students’ PE learning achievement. PE learning outcomes are more strongly influenced by the quality of the learning process, physical activity motivation, practical experience, and a supportive learning environment that encourages active student engagement.